Consensus Virtual Screening of Dark Chemical Matter and Food Chemicals Uncover Potential Inhibitors of SARS-CoV-2 Main Protease - Santibáñez-Morán, Marisa G.; López-López, Edgar; Prieto-Martínez, Fernando D.; Sánchez-Cruz, Norberto; Medina-Franco, Jose L. (ChemRxiv)
The COVID-19 pandemic caused by SARS-CoV-2 has claimed more than 380,000 lives Worldwide and more than 6.5 million people are infected. Unfortunately, there is no drug or vaccine for the treatment of COVID-19. The increasing information available of key molecular targets of SARS-CoV-2 and active compounds against related coronavirus facilitates computational tools to rapidly suggest drug candidates for the treatment of COVID-19. As part of a global effort to fight the COVID-19 pandemic, herein we report a consensus virtual screening of large collections of food chemicals and compounds classified as Dark Chemical Matter. The rationale is to complement global efforts and explore regions of the chemical space currently underexplored. The consensus approach included combining similarity searching with various queries and fingerprints, molecular docking with two docking programs, and ADMETox profiling. We propose three compounds commercially available that were sent to experimental testing. We disclose the full list of virtual screening hits that can be subject to additional selection for acquisition or synthesis and experimental testing. This manuscript will be updated when the experimental testing of the selected compounds becomes available.